Exploring the brain epitranscriptome: perspectives from the NSAS summit - Lee, Sung-Min; Koo, Bonsang; Carré, Clément; Fischer, André; He, Chuan; Kumar, Ajeet; Liu, Kathy; Meyer, Kate D.; Ming, Guo-li; Peng, Junmin; Roignant, Jean-Yves; Storkebaum, Erik; et al. (Frontiers in Neuroscience, 2023)
Increasing evidence reinforces the essential function of RNA modifications in development and diseases, especially in the nervous system. RNA modifications impact various processes in the brain, including neurodevelopment, neurogenesis, neuroplasticity, learning and memory, neural regeneration, neurodegeneration, and brain tumorigenesis, leading to the emergence of a new field termed neuroepitranscriptomics. Deficiency in machineries modulating RNA modifications has been implicated in a range of brain disorders from microcephaly, intellectual disability, seizures, and psychiatric disorders to brain cancers such as glioblastoma. The inaugural NSAS Challenge Workshop on Brain Epitranscriptomics hosted in Crans-Montana, Switzerland in 2023 assembled a group of experts from the field, to discuss the current state of the field and provide novel translational perspectives. A summary of the discussions at the workshop is presented here to simulate broader engagement from the general neuroscience field.